Musculoskeletal Disorders and their Influence on Job Performance in Security Guards of a Company in Quito 2024 - Marisol Adriana Moreno Cabezas, Sonia Elizabeth Ruiz Martínez, Mariela Alejandra Villacrés López (South Eastern European Journal of Public Health, 2025)
Musculoskeletal disorders (MSD) are a major concern in the work environment because of their considerable impact on both workers' health and productivity. This study aims to analyze how MSD affect the work performance of security guards. For this, a sample of 66 male security guards aged 19-65 was used. Participants were evaluated using two instruments: the Cornell Musculoskeletal Discomfort Questionnaire (CMDQ) and the Individual Work Performance Questionnaire (IWPQ), in order to explore the relationship between the presence of MSD and performance at work. The Chi-square and Odds Ratio tests were used for statistical analysis. The results revealed that the areas most affected by SMT were the neck, lower back and feet, with a significant relationship between SMT and negative work behavior (p = 0.019; OR 4.2), suggesting that workers with MSD are considerably more likely to exhibit negative behaviour at work such as low motivation or conflicting attitudes. In conclusion, although MSEs affect mainly key areas of the security guard corps, their direct impact on task performance and contextual performance is limited, however, significantly affects behaviour or attitudes that negatively affect performance, environment and productivity within the work environment.